Form Copy and A'-dependencies: Revisiting Resumption - Dalina Kallulli; Ian Roberts (Catalan Journal of Linguistics, 2025)
This article argues that A'-dependencies can be accounted for in terms of Form Copy (Chomsky et al. 2023). To make this argument, we draw on evidence from the distribution and interpretation of resumptive pronouns from Kallulli (2009, 2012), and we also show how the account could be extended to other phenomena, notably Left Dislocation in English. Specifically, we make the following four claims. Firstly, A'-dependencies are reducible to Form Copy. Second, we follow Kallulli’s (2009, 2012) proposal that resumption involves a pronoun in a concealed relative clause, which we model here in terms of Form Copy. Third, we show how this analysis can be extended to English Left Dislocation, bringing this construction into line with Kallulli’s analysis of resumption. Fourth, an important corollary of our approach is that Form Copy allows partial PF-copies; it relates syntactic objects, which do not have to be fully identical in formal features, still less in terms of segmental phonology. This is true not only for A'-dependencies but also for A-dependencies. The theoretical contribution of this article is thus our extension of the scope of Form Copy to A'-dependencies.